Atomically-thin Bi2MoO6 nanosheets with vacancy pairs for improved photocatalytic CO2 reduction. (July 2019) - Di, Jun; Zhao, Xiaoxu; Lian, Cheng; Ji, Mengxia; Xia, Jiexiang; Xiong, Jun; Zhou, Wu; Cao, Xingzhong; She, Yuanbin; Liu, Honglai; Loh, Kian Ping; Pennycook, Stephen J.; et al.
Abstract: Exploring efficient strategies to increase CO2 photoreduction performance is a key challenge in the energy conversion field. Herein, a cooperative role involving an ultrathin 2D structure and surface defects is employed to design defective Bi2 MoO6 ultrathin nanosheets, to boost the CO2 photoreduction activity under water with no sacrificial agent, co-catalyst or extra photosensitizer. Bi2 MoO6 ultrathin nanosheets with surface "BiO″ vacancy pairs are grown via a template-directed strategy, as proved by STEM-ADF and positron annihilation spectroscopy. The engineered "BiO″ vacancy pairs tune the local atomic structure, electronic structure of Bi2 MoO6 and serve as charge separation centers to boost the electron-hole separation. Meanwhile, the defective ultrathin structure favors the CO2 adsorption, activation and CO desorption processes. With the merits of atomically-thin configuration and surface defects, the defective Bi2 MoO6 ultrathin nanosheets display 2.55 times improved CO formation rate than their bulk counterpart under light irradiation. Graphical abstract: Image 1 Highlights: Bi2 MoO6 ultrathin nanosheets with surface "BiO″ vacancy pairs are grown via a template-directed strategy. "BiO″ vacancy pairs can be determined by STEM-ADF and positron annihilation spectroscopy. "BiO″ vacancy pairs tune the local atomic structure, electronic structure of Bi2 MoO6 and serve as charge separation centers. Defective Bi2 MoO6 ultrathin nanosheets display improved CO2 photoreduction activity than bulk counterpart.